Assessment of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status in the fine needle aspirates of metastatic breast carcinomas1. Issue 4 (1st November 2011) - Monaco, Sara E.; Wu, Yue; Teot, Lisa A.; Cai, Guoping
Abstract The assessment of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor (HER2) status in the fine needle aspirates of metastatic breast carcinomas has prognostic and therapeutic implications. In this study, expression of ER, PR, and HER2 was assessed by immunohistochemical study in 70 cases of metastatic breast carcinomas and HER2 gene amplification was further evaluated by fluorescence in situ hybridization (FISH) in 38 (54%) cases. Positive expression of ER and PR was seen in 42 (60%) and 16 (23%) cases of metastatic breast carcinomas, respectively. HER2 immunoreactivity was scored as 0/1+ in 39 (56%), 2+ in 10 (14%), and 3+ in 21 (30%) cases. HER2 gene amplification was seen in 20% of HER2 2+ and 64% of HER2 3+ cases. ER, PR, and HER2 status in primary breast cancers were available to comparison in 31 cases (44%). The concordance rates between metastatic and primary breast carcinomas were 81% for ER, 65% for PR and 71% for HER2. Our study demonstrates that ER, PR, and HER2 status can be assessed in the fine needle aspirates of metastatic breast carcinomas and ER has a higher concordance rate between metastatic and primary breast carcinomas than PR and HER2. The addition of HER2 gene amplification FISH test helps in accurate assessment of HER2 status in metastatic breast carcinomas. Diagn. Cytopathol. 2013;41:308–315. © 2011 Wiley Periodicals, Inc.